Detection of Coxiella burnettii by immunomagnetic separation-PCR in the milk of sheep in Turkey - Öngör, H; Çetinkaya, B; Karahan, M; Açik, MN; Bulut, H; Muz, A (Wiley, 2004)
[Abstract Not Available]
Keywords: Polymerase-Chain-Reaction; Q-Fever; Antibodies; Samples